Outage performance of downlink NOMA-aided small cell network with wireless power transfer - Anh-Tu Le; Dinh-Thuan Do; Munyaradzi Munochiveyi (Bulletin of Electrical Engineering and Informatics, 2021)
This article considers the outage performance of the downlink transmission for a small cell network in a heterogeneous network. Due to mobility and distribution of users, it is necessary to study massive connections and high energy efficiency for such kind of systems. To be an enabler of energy harvesting, a power beacon is helpful to support the base station to send signals to distant users, and wireless power transfer (WPT) is exploited to guarantee the data packets transmission from the power beacon to the base station. To provide massive connections, we propose a novel non-orthogonal multiple access (NOMA) technique combined with WPT to enhance outage performance and latency reduction. Furthermore, we derive outage probability (OP) to characterize the system performance. Simulation results are verified to match well between theoretical and analytical methods, and main parameters are determined to understand how they affect the proposed scheme.